Stunting and Household Food Expenditures between Junior High School Students from Smoker And Non-Smoker Families - Risky Malinda; Etti Sudaryati; Evawany Aritonang (Britain International for Academic Research (BIAR) Publisher, 2020)
Stunting is a linear growth failure due to insufficient long-term nutritional intake. The higher the proportion of household expenditure from total income, the lower the economic level of the family so it is at risk of food insecurity. This study aims to determine the differences in the proportion of stunting and household food expenditure between students from smokers and non-smokers families. This study was an observational study with a cross sectional design with a sample of 98 students from smokers 'families and 98 students from nonsmokers' families. Stunting data is obtained by measuring student height. Household food expenditure is obtained by comparing the total household expenditure spent on food with the total income earned during income. This study uses statistical analysis using the chi-square test. There was a difference in the proportion of stunting (p = <0.001) and the proportion of household food expenditure (p = <0.001) between smokers and non-smokers 'families where the proportion of stunting and household improvement was higher among smokers' families. The conclusion is there’re differences in the proportion of stunting and household food expenditure in students from smoker families and non-smoker families. Families should limit cigarette consumption and allocate appropriately in household food expenditures.